Examining the Role of Ancestral Spirits and The Mission of the Holy Spirit in The Torajan Church - Nari, Frazier (Institut Agama Kristen Negeri Toraja, 2025)
This study explores the dynamic relationship between the ancestral spirit beliefs of the Aluk To dolo tradition in Toraja and the Christian doctrine of the Holy Spirit. Using a qualitative, literature-based methodology, the research analyzes theological and cultural perspectives to understand how these two spiritual frameworks interact and influence mission dynamics. Drawing on theological literature and anthropological insights, the study examines how traditional beliefs about ancestral spirits are perceived and reinterpreted, considering Christian pneumatology. The analysis of theological literature indicates that, within certain contextual and missiological interpretations, the work of the Holy Spirit has been articulated using categories familiar to ancestral spirit beliefs, thereby opening a dialogical space between indigenous spirituality and Christian pneumatology. While the core differences between the two remain significant, especially in their understanding of divine agency and authority, the study underscores the importance of respectful engagement in mission work. It concludes that a meaningful theological dialogue must acknowledge local beliefs while offering a transformative understanding grounded in Christian theology.